Impact of channels identification and ablation in ventricular tachycardia patients through high-density mapping: preliminary experience from an Italian registry. (24th May 2021) - Scaglione, M; Calvanese, R; Pandozi, C; Pedretti, S; Rossi, L; Pelargonio, G; Mantovan, R; Solimene, F; Canciello, M; Fonte, G; Biagi, A; Caponi, D; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Ventricular tachycardia (VT) ablation techniques in ischemic cardiomyopathy have evolved during the recent years. However, the long-term success rate remains disappointing. A technique based on channel identification and ablation through a novel automated algorithm may limit the extent of ablation needed and possibly lead to higher successful rate. Purpose: To report preliminary data on feasibility and safety of a channel identification approach and to characterize late potentials (LPs) features using an ultra-high density mapping system with a novel analysis tool in ischemic VT procedures. Methods: Consecutive patients (pts) indicated for ischemic VT ablation were enrolled in the CHARISMA study. A complete map of the left ventricle was performed prior and after ablation through the Rhythmia mapping system. For our purpose channels were defined as any signal activity bounded by anatomic and functional barriers and characterized through a novel map analysis tool (Lumipoint-LM-) that automatically identifies fragmented late potentials (LPs) and continuous activation was used on the whole ventricular substrate. Procedural endpoint was the elimination of all identified conducting channels (CCs) by ablation at the CC entrance and exit followed by abolition of any residual LPs inside the CC. The ablation endpoint was noninducibility. Results: A total of 18 channels were identified through LM from 14 pts: 71.4% of the pts had 1 CC, 28.6% had 2 CCs. In the majority of the cases LPs where identified only inside CCs (57.1%), whereas in 6 cases (42.9%) LPs were present both inside and outside. The mean conduction time inside CCs was 50.3 ± 30ms, the mean CC length was 32.6 ± 17mm and the conduction velocity was 0.8 ± 0.5 mm/ms. LPs covered a mean area of 7.0 ± 5mm2 (ratio between LPs area and CCs' area = 52.4 ± 33.7%). At voltage map analysis 1 CC was present in 78.6% of the cases (2 CCs in 21.4%). LPs were identified only inside CCs in 42.9% of the cases, both inside and outside in 50% and only outside in 7.1%. Healthy tissue (voltage level≥0.5mV) was prevalent (61.2 ± 13.8%), followed by intermediate voltage areas (0.5-0.05mV; 37.5 ± 13.7%) and very low voltage areas (<0.05mV; 1.2 ± 2%). LPs were found mostly at intermediate voltage areas (54.1 ± 31.7% of the covered area; 39.1 ± 28.4% at healthy tissue and 6.8 ± 17.8% at very low voltage areas). Agreement in CCs identification between advanced analysis through LM and voltage map was fair (9/14 with complete agreement). In 3 cases voltage map overestimated LPs areas, in 2 cases failed to fully identify LPs. All CCs' entrance and exit were successfully ablated and abolition of any residual LPs inside the CC was achieved in all pts. No complication occurred. Noninducibility was achieved in all the cases. Conclusions: In our preliminary experience, a new channel identification approach through the advanced Lumipoint algorithm seems to be safe, feasible and effective at least in the acute setting of ischemic VT ablation.